A encarnação de Jesus na ótica de gênero - Zanini, Rogério Luiz (Revista eclesiástica brasileira, 2016)
When thinking or rethinking the incarnation of Jesus, his masculinity may become an issue. Feminist theologians have begun to use the gender dimension as an analytical category within a methodological principle of deconstruction and reconstruction, together with the “hermeneutics of suspicion”. They discovered that the humanity of Jesus is essential to his salvific role and recognize clearly that Jesus of Nazareth belongs to the male gender. However, they never suggest that it is Christ’s masculinity that unites the human beings with God in a salvific way. The inclusive ministry of the Kingdom of God preached by Jesus, questioned many gender stereotypes of his time and also announced an ideal inclusive church in which “there is neither Jew nor Greek, neither slave nor free man, neither male nor female ...” (Gal 3:28). And the conclusion we reached is that the faith in a God that is purely identified with the male gender is incompatible with the Christian revelation and its proposal of a totalizing and universal love.